Lie Triple Derivations on 𝒥-Subspace Lattice Algebras. (20th January 2014) - Wang, Ting; Lu, Fangyan
Abstract : We describe the structure of Lie triple derivations on 𝒥 -subspace lattice algebras. The results can be applied to atomic Boolean subspace lattice algebras and pentagon subspace lattice algebras, respectively.